Eksternalitas Usaha Budidaya Ikan Patin dalam Kolam di Kabupaten Banjar Kalimantan Selatan Externalities of Patin Fish Farming in Ponds in Banjar District, South Kalimantan - Irma Febrianty (EnviroScienteae, 2021)
The business of developing catfish in Banjar Regency since 2000 has had both positive and negative impacts on the social, economic and environmental environment. The aim of the study is to analyze the environmental externalities of catfish culture. The method used is Oppurtunity cost. The results of the analysis of the environmental externalities of the catfish culture business in the pond produced a direct positive impact, namely the emergence of catfish hatchery business, the absorption of local labor and the indirect positive impact of mud resulting from draining the fish culture pond can be used for plants and the emergence of food stalls and stalls for daily necessities and fishing ponds. The negative impact that is immediately felt by the community is runoff of pool water into the road.